2020
DOI: 10.2196/17494
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Web-Based Weight Loss Behavior Change Program With and Without Dietitian Online Coaching for Adults With Overweight and Obesity: Randomized Controlled Trial

Abstract: Background The effect of computer- or human-delivered personalized feedback on the effectivess of web-based behavior change platforms for weight loss is unclear. Objective We aimed to compare the effectiveness of a web-based behavior change intervention personalized through either computerized or human-delivered feedback with a nonpersonalized intervention in promoting weight loss in community-based adults with overweight or obesity. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 28 publications
1
66
1
Order By: Relevance
“…For example, new modes of analysis are emerging: millions of app-derived meal logs can be used to analyze a patient’s meal composition, potentially enabling automated diet recommendations [ 40 ]. Tailoring [ 41 ] and personalization [ 42 , 43 ] of BBCI in particular will profit from subgroup analyses of large data sets. In addition, research is needed on how BBCI can improve existing treatment approaches and nutrition concepts for weight management [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, new modes of analysis are emerging: millions of app-derived meal logs can be used to analyze a patient’s meal composition, potentially enabling automated diet recommendations [ 40 ]. Tailoring [ 41 ] and personalization [ 42 , 43 ] of BBCI in particular will profit from subgroup analyses of large data sets. In addition, research is needed on how BBCI can improve existing treatment approaches and nutrition concepts for weight management [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the novelty of testing a fully automated online obesity treatment with no routine adjunctive intervention from clinicians/ researchers (which typically increase engagement and weight loss) [20,21], it was also important to examine engagement metrics in this trial. To summarize patient engagement with the RxWL platform (i.e., adherence), descriptive statistics were computed for accessing the video lessons and frequency of self-reporting weight.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…They suggested that engagement with the program was higher in the platform-plus coaching group than in the platform-only group. They claimed that platform-plus coaching was related to a significantly greater chance of weight loss that is clinically meaningful (28).…”
Section: Discussionmentioning
confidence: 99%